Safety and efficacy of zero-fluoroscopy catheter ablation for paroxysmal supraventricular tachycardia in Chinese children - Cui, Xiaoran; Li, Ruibin; Zhou, Wenli; Zhang, Xiaohui; Wang, Xiaoning; Zhang, Jidong (Frontiers in Cardiovascular Medicine, 2022)
Objectives To compare the safety and efficacy of completely zero-fluoroscopy radiofrequency ablation (RFA) with that of conventional RFA guided by three-dimensional mapping in Chinese children with paroxysmal supraventricular tachycardia (PSVT). Methods The study had a single-center observational design and included 46 children aged 6–14 years who underwent RFA for PSVT at the Second Hospital of Hebei Medical University between March 2019 and September 2021. The children were divided according to whether they underwent zero-fluoroscopy RFA (zero-fluoroscopy group, n = 26) or routine RFA under X-ray guidance (conventional group, n = 20). Three-dimensional mapping was used in both groups. Baseline characteristics, total procedure time, RFA time, volume and duration of X-ray exposure, target mapping time, the immediate RFA success rate, incidence of complications, and recurrence rate were compared between the two groups. Results The children had a median age of 12 years (interquartile range 10, 13), 47.8% (22/46) were boys, and 52.2% (24/46) were girls. The mean body weight was 48.75 ± 15.26 kg. There was no significant between-group difference in the baseline data (P > 0.05). All children were followed up as outpatients at 1, 3, and 6 months postoperatively. The target mapping time was significantly longer in the zero-fluoroscopy group than in the conventional group (12.96 ± 2.24 min vs. 6.65 ± 2.56 min, P < 0.05); however, there was no significant between-group difference in the immediate success rate (100% vs. 100%), success rate at 6 months postoperatively (92.30% vs. 95.00%), complication rate (0% vs. 0.05%), recurrence rate (7.70% vs. 5.00%), RFA time (212.50 s vs. 214.00 s), or total procedure time (78.50 min vs. 74.00 min) (P > 0.05). Conclusion Zero-fluoroscopy catheter ablation can completely avoid fluoroscopy exposure in children without affecting the safety and efficacy of RFA.